Influence of a constant magnetic field on the lobster nerve: Conduction velocity and voltage clamp studies. - Schwartz, Jean-Louis. (University of Ottawa (Canada), 1977)
This thesis presents a study on the biomagnetic response of the lobster nerve. Experiments have been made on the circumesophageal connective of the lobster in order to investigate the influence of a constant intense magnetic field upon (i) the nerve impulse conduction velocity of the entire trunk by recording the compound action potentials, and (ii) the membrane potentials and the transmembrane currents under voltage-clamp conditions of the giant axon of this nerve, using the double sucrose gap technique. It was found that within the limitations of these exploratory experiments the conduction velocity, the membrane potentials and the transmembrane currents of the lobster nerve are not affected in any detectable manner by a constant 1.2 T magnetic field parallel or perpendicular to the nerve.
Keywords: Engineering, Electronics and Electrical.